PERAN KEPEMIMPINAN KOMUNIKASI KRISIS DALAM MENANGGULANGI KRISIS OPERASIONAL PLN DI KOTA MAKASSAR - Elfrianto Elfrianto; Hafied Cangara (JURNAL BADATI, 2024)
Rolling power outages in Makassar City as a result of load management due to the long dry season have caused anger among the community. A decision to turn off electricity in residents' homes from 2 to 7 hours may be unavoidable by the National Electricity Company (PLN). However, because the PLN leadership was unable to communicate during a crisis, this resulted in anger among the community.The approach used in this article is a qualitative research approach. An approach that aims to understand the phenomena experienced by research subjects by utilizing various scientific methods. The method used is an in-depth case study regarding load management and power outages in Makassar City. The results shown are that PLN failed to predict the unclear conditions at the start of the crisis and also failed to build communication with the city government and the community. They do not provide good information and explanations that can be accepted by the public.